Effect of topical application of 5-FU on the corneoscleral limbus of rabbits - Ferraz, Lucieni C.B. [UNESP]; Schellini, Silvana Artioli [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (My University, 2007)
• Aim: To observe the effects of topical application of 5-fluorouracil (5-FU) on the rabbits corneal limbus. • Methods: 5-FU was applied topically to the corneoscleral region of rabbits eyes. The animals were sacrificed immediately or 7, 15, 30 and 60 days later, and tissues were submitted to histological examination. • Results: All animals presented corneoscleral deepithelization close to the site of application during the immediate post-operative period, whereas on the 4th postoperative day ulceration was no longer present. Histological examination showed absence of epithelium and slight edema. After one week (G2), 2 animals presented epithelial defects, thickened epithelium with larger basal cells and loose chromatin, and slight subepithelial edema. The remaining groups showed no alterations. • Conclusion: The 5-FU topically on the corneoscleral limbus postpone the epitelization.
Keywords: 5-fluorouracil; Antimitotic agent; Histopathology; Rabbits; Topical application; fluorouracil; animal experiment; animal model; animal tissue; controlled study; cornea edema; cornea epithelium; cornea limbus; drug effect; histology; nonhuman; postoperative period; rabbit